Identification of Functional Groups of Rapitest Luster Leaf Products for Soil Phosphorus Testing Based on Color Changes using Fourier Transform Infrared Spectroscopy (FTIR) - Asriyani, Nur; Rahmawati, Hilda (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Phosphorus is an important nutrient for plants and is useful as the main driver of primary productivity in plants. Periodic soil phosphorus testing is essential to monitor the availability of phosphorus in the soil so that it is not excessive or reduced to achieve maximum productivity. Testing using laboratory methods takes a long time and is expensive. Rapitest Luster Leaf is a soil testing product based on color changes using a colorimetric method of mixing reagents and color indicators that is practical, easy, portable, and can be used directly on agricultural land. Identification of Rapitest functional groups using FTIR is carried out to predict compound content as a renewable material for soil testing. The analysis showed that the functional groups formed include SO42, which occurs at 987, 631, and 602 cm-1 vibration waves. It indicates that the vibration is shifting to the right. At vibrations of 677-573 cm-1, the absorption of the Na2SO4 compound occurs. Sodium sulfate is predicted to be a reagent compound contained in Rapitest. At 811-901 cm-1 and 3524-3209 cm-1 vibration waves, functional group bonds of Mo-O and N-H are formed, respectively. The molecular bonds formed predict that ammonium molybdate is the color indicator compound used.